School variables on junior secondary school students mathematics performance in Cross River State, Nigeria - Opie, O.N.; Ovat, S.V.; Meremikwu, A.N. (2014)
N/a
Keywords: Assessment; Learning outcomes; Mathematics education; Secondary education; _C:Nigeria; _authorsString:Second,A.B.; _checkedWith:AERD; _research:Quantitative; _type:Peer-reviewed article